BENEFITS OF MENTAL SPORTS AND THEIR INFLUENCE ON THE ACADEMIC PERFORMANCE OF THE STUDENTS - Calunsag, Buena D (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to ascertain the advantages of mental sports and how they might affect the academic performance of the chosen students in Dumingag, Zamboanga Del Sur, for the 2019-2020 school year. All BPED I to IV students from a chosen Dumingag, Zamboanga del Sur institution were enrolled as student participants. The questionnaire checklist served as the primary instrument used by the researcher to collect the necessary data using the descriptive survey approach. Frequency counts, percentages, and weighted arithmetic mean (WAM) were used to evaluate and interpret the data collected. The findings indicated that half of the individuals aged 18 to 19 were female and actively participated in mental sports. As a result, neither the participant's gender nor age impacts how well they perform academically in mental sports. Additionally, the study showed that the participants believed practicing mental sports gave them a lot of advantages, and one of those was excellent academic performance. However, no discernible link existed between the students' regular participation in mental sports and academic success.